Analysis of Matrix Organizational Structure Implementation in Achieving Company Strategic Objective - Virollina, Cut; Nasution, Yasmine (International Journal of Social Service and Research, 2023)
Several researchers assert that the matrix structure has the capacity to exert a substantial impact on implementation strategies; however, its complexity presents numerous obstacles that may result in significant decision-making delays and even financial losses for the organization. This research was aims to analyze the application of a matrix structure in a company that changes its organizational structure to a matrix in order to achieve its strategic goals. The research method used was a qualitative descriptive analysis method with a case study approach at a health institution, a company that has implemented a matrix organizational structure for three years. The CIPP concept framework (context input, process, product) was used as a tool for collecting primary data through in-depth interviews with the board of directors and management that supports several directorates, as well as secondary data through document review. The data analysis process was carried out using the content analysis method. This study has identified important steps that organizations must take when implementing change management initiatives through the implementation of a matrix organizational structure to effectively achieve their strategic goals. However, strong leadership must be present throughout the change process to ensure the achievement of organizational goals. The findings from this research are expected to be useful for institutions that change their organizational structure to a matrix to build synergy and manage challenges to achieve their strategic goals.